2009 IEEE/SP 15th Workshop on Statistical Signal Processing 2009
DOI: 10.1109/ssp.2009.5278458
|View full text |Cite
|
Sign up to set email alerts
|

Linear unmixing of hyperspectral images using a scaled gradient method

Abstract: This paper addresses the problem of linear unmixing for hyperspectral imagery. This problem can be formulated as a linear regression problem whose regression coefficients (abundances) satisfy sum-toone and positivity constraints. Two scaled gradient iterative methods are proposed for estimating the abundances of the linear mixing model. The first method is obtained by including a normalization step in the scaled gradient method. The second method inspired by the fully constrained least squares algorithm includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…The Fully Constraint-Scale Gradient Method (FC-SGM) has been proposed in [18] as an alternative of FCLS to solve the linear unmixing problem under the non-negativity and sumto-one constrains using the scaled gradient method The criterion to be optimized is derived from the Lagrangian formulation including the non-negativity constraint. Then this criterion is minimized thanks to an iterative scaled gradient method.…”
Section: Fc-sgmmentioning
confidence: 99%
“…The Fully Constraint-Scale Gradient Method (FC-SGM) has been proposed in [18] as an alternative of FCLS to solve the linear unmixing problem under the non-negativity and sumto-one constrains using the scaled gradient method The criterion to be optimized is derived from the Lagrangian formulation including the non-negativity constraint. Then this criterion is minimized thanks to an iterative scaled gradient method.…”
Section: Fc-sgmmentioning
confidence: 99%
“…In addition, several hyperspectral imaging-based spectral unmixing algorithms have been gradually introduced into MODIS FSC mapping. Zhang et al (2015) produced MODIS FSC maps using a fully constrained least squares spectral mixture analysis method (FCLS) [30], fully constrained scaled gradient method (FCSGM) [31], a sparse regression method (SPARSE) [32] and a polynomial nonlinear method (POLY) [33,34] for the Tibetan Plateau. Although they found that all of these algorithms can improve the accuracy of snow-cover mapping compared with the MOD10A1 FSC, they also showed that complex terrain can greatly reduce the accuracy of these spectral unmixing algorithms [35].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are described in Heinz & Chang 2001;Theys et al 2009). For instance, the New Concepts in Imaging: Optical and Statistical Models FCLS method presented in (Heinz & Chang 2001) estimates the abundances by minimizing a mean-square-error criterion subject to linear equality and inequality constraints.…”
Section: Introductionmentioning
confidence: 99%